Problematika Sosial Dalam Film The Flu Serta Implikasinya Terhadap Pembelajaran Drama Di SMA - Dila Afriliyana; Yuliati Eka Asi; Patrisia Cuesdeyeni; Jumadi Jumadi; Hadilah Hadilah; Erviana Nurani (Universitas Palan, 2023)
The general research objective is to obtain an overview of social problems in a film and their implications for learning in high school. This study uses a descriptive qualitative approach, in which the researcher records carefully and accurately the data in the form of words, sentences, pictures, and videos contained in the film. The use of a descriptive qualitative approach in this study aims to describe social problems such as social problems of biological factors, economic factors, psychological factors, and cultural factors in The Flu film. Researchers found 51 social problems in the film The Flu and have described their implications for drama learning in high school. The most common social problems found are social problems of biological factors consisting of 21 data, social problems of psychological factors consisting of 20 data, social problems of economic factors consisting of 5 data and social problems of cultural factors consisting of 5 data. The Flu film provides many descriptions of social problems that can be used as knowledge for students at school. Therefore, in learning drama, this film can be used as an alternative teaching material, especially in discussions about examining storylines, act by act, and conflicts in drama texts in the form of scripts or stages and presenting plays in the form of stages or scripts.